Slovenian legal language from the standpoint of a Slovenian language expert - Žele, Andreja (Linguistica (Ljubljana), 2013)
The paper draws attention to the current issues of legal language use within one's own language, in this case Slovenian. We use specific cases to point out the additional semantic stress on legal terminology, word-formational variations and their (non-)acceptability, the need to take into consideration grammatical categories such as semantic definiteness in adjectives, and perfective and imperfective aspects in verbs and gerunds, as well as the (non-)justification of conversions within multiword legal terms. In this regard it is established that whatever is ambiguous in legal terminology is at the same time also wrong. Comment is made on the lexico-grammatical response of legal Slovenian to the inclusion of concepts of the transnational legal order, i.e. the legal order of the European Union. The analysis uses Slovenian legal texts and translated legal texts all approved by the competent legal institutions for linguistic analysis and the legal lexis which had already been included in language-oriented discussions. According to the issues presented, the study of law (i.e. legal norms, legal science and legal practice) reveals a constant need, or rather impetus, to introduce a parallel study course dealing with regular language based and linguistic updates of legal Slovenian.
Keywords: ambigous; dvoumnosti; langage juridique; langue juridique; law; legal language; legal terminology; pravni jezik; pravo; Slovene; Slovene language; slovenščina; terminologie juridique; terminologija; terminology